A qualitative exploration of the client experience of inter-professional practice in the delivery of ActivePlus: a combined smoking cessation and physical activity intervention - G. A. O'Sullivan; Clare Hanlon; T. Dentry; T. Morris; L. Banting (BMC, 2018)
Abstract Background Research investigating interprofessional practice (IPP) frameworks has predominately focused on the service delivery of IPP or educating practitioners through interprofessional education. Minimal research has addressed client outcomes or the experience of clients with IPP in real world contexts. In this paper, we explore the experience of seven participants in the ActivePlus program, an IPP-based smoking cessation intervention combined with physical activity promotion. Methods Participants informed on their program experiences through post-program in-depth interviews. A thematic analysis drew out themes pertaining to participant experiences of the joint practice element of the IPP model of care. Results Analysis identified two major themes: the joint practice experience, and the client-centered approach of the IPP model of care. Participants reflected on the ways that having two health practitioners in joint sessions benefited their intervention experience, as well as providing some critical feedback. Participants also reported observing and valuing aspects of client-centered practice that strengthened the rapport within the practitioner-client team and aided their behaviour change progress. The client-centered practice was instrumental in overcoming initial teething issues with joint session delivery and alleviating pre-program participant concerns about being outnumbered by multiple practitioners. Conclusion Despite some early teething issues, participants reported a positive acceptance of the IPP and joint session delivery model, which added value to the overall ActivePlus program. Results from this research can provide practitioners with a client perspective on the key aspects they perceive as important in IPP joint session delivery. Further investigation into the client perception in similar interventions is recommended with larger samples and non-clinical groups.